2020
DOI: 10.1002/cbin.11315
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule stabilizer epothilone B as a motor neuron differentiation agent for human endometrial stem cells

Abstract: Microtubule-stabilizing agents (MSAs), until now, have primarily been considered for their anti-proliferative effects in the setting of cancer. However, recent studies have revealed that one particular MSA, epothilone B (EpoB), can promote axonal regeneration after traumatic spinal cord injuries (SCI) even in the presence of inhibitor molecules such as neurite outgrowth inhibitor-A (Nogo-A). On the basis of the importance of having an efficient motor neuron (MN) differentiation protocol for stem cell therapy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 61 publications
(67 reference statements)
0
11
0
Order By: Relevance
“…The mean porosity and pore size of fabricated neural guidance conduit (NGC) was 69 ± 4.5% and 11.1 ± 2.1 nm which proved this NGC could be utilized as a promising strategy to bridge the gap between severed peripheral nerve stumps for the treatment of damaged nerves that the results confirmed designed nerve conduit fabricated by electrospinning with tailored mechanical strength, hydrophilic/hydrophobic property and desirable cell adhesion properties could be an efficient alternative to autograft for peripheral nerve regeneration research. Due to its advantage of high‐surface area and existence of bioactive inorganic ions respectively for cell attachment and tissue regeneration, it is believed that this electrospun nerve conduit could find more application on behalf of nerve regeneration in future, to further improve functional regeneration outcome especially for longer nerve defect restoration 7‐10,41 …”
Section: Resultsmentioning
confidence: 99%
“…The mean porosity and pore size of fabricated neural guidance conduit (NGC) was 69 ± 4.5% and 11.1 ± 2.1 nm which proved this NGC could be utilized as a promising strategy to bridge the gap between severed peripheral nerve stumps for the treatment of damaged nerves that the results confirmed designed nerve conduit fabricated by electrospinning with tailored mechanical strength, hydrophilic/hydrophobic property and desirable cell adhesion properties could be an efficient alternative to autograft for peripheral nerve regeneration research. Due to its advantage of high‐surface area and existence of bioactive inorganic ions respectively for cell attachment and tissue regeneration, it is believed that this electrospun nerve conduit could find more application on behalf of nerve regeneration in future, to further improve functional regeneration outcome especially for longer nerve defect restoration 7‐10,41 …”
Section: Resultsmentioning
confidence: 99%
“…Lentivirus (second-generation) was utilized for GFP transduction of hEnSCs, based on a previous study. 29 For this purpose, plasmid pCDH-Cop GFP-Pru was used comprising EF-1α promotor to upgrade the GFP transgene expression. HEK293 T cell line was cultured and transfected with the vector linked with a pMD2.G as an envelope plasmid and psPAX2 packaging plasmid using the calcium phosphate precipitation method.…”
Section: Enscs Green Fluorescent Protein (Gfp) Transductionmentioning
confidence: 99%
“…Up to now, there are no effective treatments for full functional retrieval after an SCI for the limited regeneration ability of the CNS. One potential solution is the development of stem cell differentiation to substitute damaged and lost cells following SCI (Mahmoodi et al, 2020). Recent studies have shown that the use of predifferentiation stem cells before transplantation can reduce the risk of stem cell proliferation or their migration to inappropriate areas of the CNS that may lead to severe dysfunction or F I G U R E 8 The results of quantitative real-time PCR analysis on day 14 for neural markers in hEnSCs after incubation with the two utilized neuronal differentiation media (with and without 17β-estradiol).…”
Section: Expression Of Neuron-like Cell Markersmentioning
confidence: 99%